Doxycycline Treatment of Mansonella perstans–Infected Individuals Affects Immune Cell Activation and Causes Long-term T-cell Polarization. (3rd June 2022) - Aniagyei, Wilfred; Adjei, Jonathan Kofi; Adankwah, Ernest; Seyfarth, Julia; Mayatepek, Ertan; Antwi Berko, Daniel; Sakyi, Samuel Asamoah; Batsa Debrah, Linda; Debrah, Alexander Yaw; Hoerauf, Achim; Owusu, Dorcas O; Phillips, Richard O; et al.
Abstract: Background: Doxycycline is used for treatment of Mansonella perstans infection. Immune modulatory effects of both M. perstans and doxycycline have been described but long-term implications on host immune response are not defined. Here we determined multiple immune parameters of M. perstans– infected individuals before and after doxycycline treatment to characterize doxycycline effects on host T-cell immunity. Methods: Immune characterization of doxycycline-treated M. perstans– infected individuals was performed as part of an open-label randomized clinical trial. Immune cell population phenotyping by flow cytometry and functional in vitro T-cell assays were performed at baseline, 6 months, and "long term" (18–24 months) after treatment start. Treatment efficacy, based on peripheral blood microfilaria (mf) burden, was correlated with immune parameters and effects on immune response against concomitant Mycobacterium tuberculosis infection were determined. Results: Immune population phenotyping indicated changes in functional T-cell responses after doxycycline treatment. Constitutive and superantigen-induced T-cell activation and polarization towards T-helper type (TH ) 1 phenotype at baseline declined after doxycycline treatment, whereas low proportions of TH 17 and TH 1* cells at baseline increased significantly at follow-up. In accordance, long-term decline in antigen-specific TH 1 responses against concomitant M. tuberculosis infection was seen. Notably, only TH 17 and TH 1* changes after 6 months and TH 17 at baseline were negatively correlated with M. perstans microfilaria burden or reduction, whereas long-term changes were not associated with treatment efficacy. Conclusions: We found long-term immune modulatory effects of doxycycline treatment leading to decreased constitutive T-cell activation, polarization towards TH 17/TH 1*, and impaired immune response against concomitant M. tuberculosis infection. Abstract : Doxycycline caused modulation of T-cell activation and polarization with functional implications on concomitant Mycobacterium tuberculosis infection in Mansonella perstans –infected individuals. Immunological changes were detectable long term after treatment and were largely independent from anti-microfilaria treatment efficacy.